2016
DOI: 10.1021/acs.jpcb.6b10387
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Favorable Aggregation of Monolacunary Keggin Anions

Abstract: We here present a series of classical molecular dynamics simulations (MD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 91 publications
0
18
0
2
Order By: Relevance
“…Information on dynamic processes of POM-cation interactions can be accessed by classical and ab initio molecular dynamics (MD) simulations. [55][56][57][58] For example, MD was used in conjunction with the above-mentioned microscopy study, and both independently showed formation of POM-pairs linked by Na + , also consistent with the solid-state structure. [51] In summary, the combination of experiment and theory can potentially provide powerful and accurate information about POM-cation interactions in solution, guiding future developments of new POM architectures and superstructures.…”
Section: Experimental and Theoretical Methods To Explore Cation-pom Amentioning
confidence: 56%
See 1 more Smart Citation
“…Information on dynamic processes of POM-cation interactions can be accessed by classical and ab initio molecular dynamics (MD) simulations. [55][56][57][58] For example, MD was used in conjunction with the above-mentioned microscopy study, and both independently showed formation of POM-pairs linked by Na + , also consistent with the solid-state structure. [51] In summary, the combination of experiment and theory can potentially provide powerful and accurate information about POM-cation interactions in solution, guiding future developments of new POM architectures and superstructures.…”
Section: Experimental and Theoretical Methods To Explore Cation-pom Amentioning
confidence: 56%
“…Thereby, experimentally accessible data such as vibrational or electronic absorption properties can be calculated from first principles, and characteristic features of the POM–cation interactions can be identified. Information on dynamic processes of POM–cation interactions can be accessed by classical and ab initio molecular dynamics (MD) simulations . For example, MD was used in conjunction with the above‐mentioned microscopy study, and both independently showed formation of POM‐pairs linked by Na + , also consistent with the solid‐state structure .…”
Section: Introduction: Fundamentals Of Pom–cation Interactionsmentioning
confidence: 99%
“…We also show that these supramolecular systems are prone to aggregation according to the solvent composition and demonstrate that the difference in the nature of the POM, the charge of the metal linker or the solvent composition considerably affects the supramolecular organization, which in some cases lead to the formation of molecular gels retaining the initial nanostructuration. Since in previous studies some of us and other authors have shown that molecular dynamics (MD) simulations provided unique insight into the origin of POMs/counter-cation interactions, [27][28][29][30][31][32] we show here that the solvent plays a key role by modulating ionpairing and thus self-assembly.…”
Section: Introductionmentioning
confidence: 59%
“…Dadurch können experimentell beobachtbare Daten wie Schwingungs‐ und elektronische Absorptionsspektren basierend auf Ab‐initio‐Methoden berechnet und charakteristische Eigenschaften der POM‐Kation‐Wechselwirkungen identifiziert werden. Informationen über dynamische Prozesse der POM‐Kation‐Wechselwirkungen können zudem durch klassische und Ab‐initio‐Moleküldynamik(MD)‐Simulationen zugänglich gemacht werden . So wurde z.…”
Section: Einleitung: Grundlagen Der Pom‐kation‐wechselwirkungenunclassified
“…Informationen über dynamische Prozesse der POM-Kation-Wechselwirkungen kçnnen zudem durch klassische und Ab-initio-Moleküldynamik(MD)-Simulationen zugänglich gemacht werden. [55][56][57][58] So wurde z. B. MD zusammen mit der oben beschriebenen Mikroskopiestudie genutzt, um unabhängig voneinander die Bildung von Na + -verknüpften POM-Paaren nachzuweisen, was auch konsistent mit der beobachteten Festkçrperstruktur war.…”
Section: Lçslichkeit Und Ionenpaarbildungunclassified